2022
DOI: 10.1021/acs.est.2c03633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of C/Mn Ratios on the Sorption and Oxidative Degradation of Small Organic Molecules on Mn-Oxides

Abstract: Manganese (Mn) oxides have a high surface area and redox potential that facilitate sorption and/or oxidation of organic carbon (OC), but their role in regulating soil C storage is relatively unexplored. Small OC compounds with distinct structures were reacted with Mn(III/IV)-oxides to investigate the effects of OC/Mn molar ratios on Mn−OC interaction mechanisms. Dissolved and solid-phase OC and Mn were measured to quantify the OC sorption to and/or the redox reaction with Mn-oxides. Mineral transformation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…For instance, introducing organic acids can modify the relative rates of olation and oxolation reactions, causing the transformation of ferrihydrite into goethite, magnetite, and lepidocrocite, facilitated by the formed Fe(II) [ 67 ]. Similarly, partial reduction of Birnessite by organic carbon can increase the proportion of Mn(II, III) on the edge sites of Birnessite and further lead to the formation of MnOOH and Mn 3 O 4 [ 18 , 20 , 66 , 70 , 73 , 74 ].…”
Section: Interactions Between Minerals and Socmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, introducing organic acids can modify the relative rates of olation and oxolation reactions, causing the transformation of ferrihydrite into goethite, magnetite, and lepidocrocite, facilitated by the formed Fe(II) [ 67 ]. Similarly, partial reduction of Birnessite by organic carbon can increase the proportion of Mn(II, III) on the edge sites of Birnessite and further lead to the formation of MnOOH and Mn 3 O 4 [ 18 , 20 , 66 , 70 , 73 , 74 ].…”
Section: Interactions Between Minerals and Socmentioning
confidence: 99%
“…For organic carbon, the co-precipitation with iron minerals will alter its biogeochemical cycling, offering higher stability against leaching, runoff, and biodegradation [ 194 , 202 , 205 , 207 , 208 ]. Mn minerals can also be co-precipitated with organic carbon during the oxidative precipitation of Mn(II) [ 18 , 20 ], although fewer studies have been reported. Metals such as Ca and Al can be precipitated with alkalinity and involve organic carbon to form co-precipitates, while only several studies reported the formation of Ca-organic carbon [ 209 , 210 ] or Al-organic carbon coprecipitates [ 48 , 211 ], as they assumably often remain in the soluble form in the environment.…”
Section: Interactions Between Minerals and Socmentioning
confidence: 99%
See 3 more Smart Citations